Using Traffic Simulation for Level of Service Traveller Perception Studies - Piva, Fernando Jose; Setti, José Reynaldo; Washburn, Scott (Promet - Traffic&Transportation, 2022)
Level of service (LOS) classifications of traffic oper-ational conditions play a significant role in roadway-im-provement funding decisions. Traveller perception of LOS should be consistent with traffic analysis values to avoid undermining the public confidence in the transpor-tation agency decisions. Research methods to study trav-eller perceptions range from in-vehicle videos to focus groups and surveys. These methods have different advan-tages, but all suffer from time and/or cost inefficiencies for collecting data sets across a wide range of operating conditions. This paper describes a novel method to study this topic with increased time and cost efficiency. This new method combines traffic microsimulation and 3-D visualisation capabilities. The focus of this paper is to provide guidance on how to apply traffic microsimula-tion and computer 3-D visualisation to evaluate highway trip quality from a traveller’s perspective. It discusses the creation of the simulation environment to produce a real-istic view from the vehicle’s cabin interior, including the network creation, landscaped area, dashboard speedom-eter, and rear-view mirror. The authors also propose an automated method for choosing an appropriate vehicle within the simulated traffic stream, such that the desired overall traffic stream conditions are conveyed to the trav-eller vehicle within the field of view.